Comparative constitutional law in Latin America - Dixon, Rosalind; Ginsburg, Tom, 1967- (Edward Elgar Publishing, 2017)
This book provides unique insights into the practice of democratic constitutionalism in one of the world's most legally and politically significant regions. It combines contributions from leading Latin American and global scholars to provide 'bottom up' and 'top down' insights about the lessons to be drawn from the distinctive constitutional experiences of countries in Latin America. In doing so, it also draws on a rich array of legal and interdisciplinary perspectives. Ultimately, it shows both the promise of democratic constitutions as a vehicle for social, economic and political change, and the variation in the actual constitutional experiences of different countries on the ground - or the limits to constitutions as a locus for broader social change. This book presents new perspectives on recurrent topics and debates that enrich comparative constitutional law in other regions of the world, both in the Global South and the Global North. The fine-tuned, in-depth approach of the contributors brings rigorous scholarship to this institutionally diverse and significant region, illuminating the under-explored relationship between constitutionalism, politics, ideology and leadership. This unique and challenging study will prove to be an indispensable tool, not only for academics interested in Latin America but for comparative constitutional law scholars across the globe.